Territórios dissidentes: espaços da loucura na cultura urbana contemporânea - Bordignon, Gabriel Barros (2015)
The idea of madness is present in our society through association with the different, unusual, improper; any expression that does not suit in the social norms that seem so natural. The idea of madness varied in history according to the changes occurring in every society and times. Madness has always had a social space in human history, and has always had its physical spaces. The association between architecture and madness is generally represented by the emblematic figure of the asylum, although this type is in process of extinction in several countries, among them Brazil. Madness, throughout history, have had various forms of understanding and, therefore, there were also several spaces of madness in gradual process of evolution to the present day. In order to understand the changing character of madness spaces, accompanied by social transformations, ideas about the person called crazy and of the history of architecture, this dissertation discusses, at first, the madness spaces before modernity, where it will seek to show the different understandings about the madness, the spaces that generated such ideas and the changes that were taking them at different times. In a second step, will show the spaces of madness during modernity, addressing how the scientific and technological advances, social, economic and political changes influenced the creation of architectural typology of asylum, which is still imagery icon of a space of madness . In a third time, will show some movements of psychiatric reform of the world, as well as the Centers for Psychosocial Care (CAPS), urban facilities nationals of replacement to the type asylum, contrary to the jail and seeking a return to the community life of madness, coexistence in society and in the urban space. Finally, will be presented two case studies, contemporary brazilians that are evident on the differences with the prevailing models of care in country: the Trilhas AT Group of Uberlândia - MG, which has the situationist dérive as therapeutic experience and city reading; and the TAMTAM Group of Santos - SP, with its inclusion work shares its space constructed from art, culture, community life and especially the theater. The objects of study In-depth in the fourth chapter are understood and termed as dissident experiences, stand out from the model set out in Brazil psychosocial care; seen therefore as relevant references in the current scenario of the relationship between madness, city and contemporary urban culture in the country. Intends to make relations between the spaces studied in different periods, reflecting on the role of architecture in the process of transformation of the concept of madness. Presenting different historical and philosophical moments, the work aims to show that architecture, much more than a silent spectator, it is also agent in the evolutionary process of the idea of madness and its relation to society.